The myocardial infarction-associated transcript 2 inhibits lipid accumulation and promotes cholesterol efflux in oxidized low-density lipoprotein-induced THP-1-derived macrophages via inhibiting mitogen-activated protein kinase signaling and activating the nuclear factor erythroid-related factor 2 signaling pathway. Issue 1 (1st January 2022) - Mu, Fangxiang; Wang, Yuqing; Wu, Hong; You, Qingxia; Zhang, Daimin
ABSTRACT: Dysregulated lipid metabolism of macrophages contributes to thrombosis and antiphospholipid syndrome (APS). The long non-coding RNAs (lncRNA) myocardial infarction-associated transcript 2 (Mirt2) has been reported to inhibit inflammation and lipid accumulation; therefore, this study intended to clarify whether Mirt2 served a role in lipid metabolism. THP-1-derived macrophages with or without Mirt2-knockdown or overexpression, were exposed to oxidized low-density lipoprotein (ox-LDL), then cell migration, lipid accumulation, cholesterol efflux and inflammation were assessed using wound healing, oil red staining, commercial kits and western blot assays. Besides, ML385 was used to treat THP-1-derived macrophages to inhibit nuclear factor erythroid-related factor 2 (NRF2) expression. The expression of proteins involved in the above processes were measured by western blot. Results demonstrated that phorbol 12-myristate 13-acetate (PMA) significantly increased Mirt2 expression in THP-1 cells. Mirt2-knockdown enhanced ox-LDL-induced macrophage migration, lipid accumulation, inflammation, and inhibited cholesterol efflux. By contrast, Mirt2 overexpression displayed the opposite effects. Furthermore, Mirt2-knockdown inhibited NRF2 signaling and enhanced mitogen-activated protein kinase (MAPK) signaling, while Mirt2 overexpression displayed the opposite effects. Finally, the NRF2 inhibitor ML385 significantly reversed the above effects of Mirt2. In summary, Mirt2 served an important role in regulating lipid metabolism in macrophages via inhibiting MAPK signaling and activating the NRF2 signaling pathway.